Validating Communicative Tests of Reading and Language Use of Classical Greek. Issue 45 (2022) - Coniam, David; Poupounaki-Lappa, Polyxeni; Peristeri, Tzortzina
Abstract: This paper builds on the work presented previously in this journal by Poupounaki-Lappa et al. (2021 ), which described the development of a communicative test of Reading and Language Use of Classical Greek calibrated to the Common European Framework of Reference (CEFR) at levels A1 and A2 (Council of Europe, 2001 ). In the current paper, the two tests of Classical Greek are calibrated both together and to the CEFR. In addition to describing the methodology for comparing the two separate tests of Classical Greek, the paper is also designed to be of interest to educators of other classical languages. It is hoped that they may find it useful not only by facilitating robust test design, but also by demonstrating the methods by which tests can be linked together on a common scale (as with the CEFR) or linking tests one to another (e.g., different end-of-year tests, at different points in time).